Introducing a novel 3D Chen-Rössler map for NTRU-based image encryption with OFDM transmission over a noisy channel - Alain F. Djomo; Lee Mariel H. Yepdia; Yannick P. K. Nkandeu; Yannick A. Abanda; Alain Tiedeu (Discover Electronics)
Abstract Data integrity and security issues are worsening with the emergence of new technologies such as 5G, IoT, AI, and Cloud. Traditional encryption algorithms, such as AES and RSA, show limitations in the face of modern threats, not least because of their vulnerability to quantum computers. Hybrid solutions are therefore being considered. Post-quantum cryptography is emerging as a new way of guaranteeing data security in transit in the cloud. NTRU (Nth degree Truncated polynomial Ring Unit) is a promising algorithm in this new branch of cryptography. It requires further research to overcome its weaknesses, notably the lack of security standards. In this paper, we propose an image encryption algorithm based on generating a new chaotic system exploited for image encryption using NTRU. The encryption and decryption processes built around the NTRU algorithm are inserted into an orthogonal frequency division multiplexing system (i.e., the crypto-OFDM system) for secure image transmission in a non-secure channel. The proposed encryption algorithm demonstrates remarkable robustness against statistical and differential attacks, with an entropy close to 8, an NPCR of 99.6563% and a UACI of 33.5861%, while ensuring a processing time reduced to just 0.053 s. Its efficiency is also confirmed by advanced quality measurements, including PSNR values of 84.2544 dB and 72.1794 dB, illustrating exceptional visual fidelity after decoding. Integrated with an FFT-OFDM transmission system, it clearly outperforms the DCT-OFDM variant in terms of noise robustness and bit error rate reduction, paving the way for secure, high-performance communications.